Analisis Perubahan Kandungan Asam Lemak Bebas pada Nasi Lalapan yang Menggunakan Minyak Goreng Berulang di Pedagang Kaki Lima Kota Malang - Widi Rimastuti; Rina Rifqie Mariana; Aisyah Larasati (Teknologi dan Kejuruan: Jurnal Teknologi, Kejuruan, dan Pengajarannya, 2019)
This research aimed to (1) find the change in free fatty acid content in "nasi lalapan" that used repeated cooking oil, (2) the content difference of "nasi lalapan" from each oil repetition. This research was experimental using a quantitative approach. The target of this research was "nasi lalapan" street vendors in Malang City. The samples were taken from one vendor in one sub-district. The samples were fried chicken, fried catfish, and fried tempeh in the 0, 5th, 10th, and 20th frying and were tested in the laboratory to find the free fatty acid content change. The data analysis in this research used the ANOVA test and further LSD test. The results showed that (1) free fatty acid in fried chicken, catfish, and tempeh increased along with the frying repetition, (2) the usage of repeated cooking oil influenced the free fatty acid content.